Analysis of the throughput in full-duplex WLAN - Chen ZHAO; Yunzhou LI; Xibin XU; ANGJing W (Dianxin kexue)
WLAN is one of the important ways of accessing mobile internet.However，the performance of WLAN declines rapidly as the number of users increases.Improving the performance of WLAN with high density deployment is an important research direction of WLAN technology.Distributed coordination function（DCF）which was the basic media access method of IEEE 802.11 in infrastructure-based networks was modeled and the bottleneck of downlink throughput was pointed out.Taking advantage of full-duplex technology where there was a breakthrough in recent years，a new MAC protocol was designed and analyzed.By providing the AP full-duplex transmitting ability and simple modifications to traditional DCF protocol，the new protocol made the downlink throughput breaking through the bottleneck in infrastructure-based WLAN and increased the total throughput by more than 60%.